A review and empirical comparison of motivation scoring methods: An application to self-determination theory - Howard, J.L.; Gagné, Marylène; Van den Broeck, A.; Guay, F.; Chatzisarantis, Nikos; Ntoumanis, Nikos; Pelletier, L.G. (SPRINGER/PLENUM PUBLISHERS, 2020)
© 2020, Springer Science+Business Media, LLC, part of Springer Nature.